2006
DOI: 10.1007/bf02704606
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclays for polymer nanocomposites, paints, inks, greases and cosmetics formulations, drug delivery vehicle and waste water treatment

Abstract: An overview of nanoclays or organically modified layered silicates (organoclays) is presented with emphasis placed on the use of nanoclays as the reinforcement phase in polymer matrices for preparation of polymer/layered silicates nanocomposites, rheological modifier for paints, inks and greases, drug delivery vehicle for controlled release of therapeutic agents, and nanoclays for industrial waste water as well as potable water treatment to make further step into green environment. A little amount of nanoclay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(160 citation statements)
references
References 54 publications
(45 reference statements)
4
151
0
5
Order By: Relevance
“…Cloisite Na + , which is a Montmorillonite (MMT) sodium nanoclay ( Fig. 1), was used as a nano filler to reinforce ABPBI membrane, due to its high aspect ratio and low price [16] [17]. It was reported that sulfonated MMT was used to balance the ionic conductivity and mechanical properties of the composite membranes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Cloisite Na + , which is a Montmorillonite (MMT) sodium nanoclay ( Fig. 1), was used as a nano filler to reinforce ABPBI membrane, due to its high aspect ratio and low price [16] [17]. It was reported that sulfonated MMT was used to balance the ionic conductivity and mechanical properties of the composite membranes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effect of aluminium hydroxide, antimony trioxide and EVA on the properties of silane crosslinked LDPE was investigated [10]. It has been reported that using layered silicates with large aspect ratios (a few nanometer thick but hundreds to thousands of nanometers long) in a polymer matrix improves mechanical properties [11][12][13], reduces thermal expansion coefficient [14], gas permeability [15] and flammability [16,17] of the polymer. These improvements can be achieved by using small amounts of nanofiller (≤5%) compared to ~40% for micro-fillers.…”
Section: Introductionmentioning
confidence: 99%
“…These nanomaterials are among the most widely used in industry and are under development as drug delivery systems and in polymer nanocomposites with industrial and biomedical applications (Patel et al, 2006;Pavlidou and Papaspyrides, 2008). Both nanoparticles are comprised of plates approximately 1-2 nm in thickness and 30-100 nm in diameter ( Fig.…”
Section: Resultsmentioning
confidence: 99%